(untitled) (Research, Society and Development, 2020)
The present research was constituted in a bibliographic study about the management by competences in human resources in organizations in general. Addressing concepts of competence that should be understood as a set of human capacities that justify high performance by means of skills, knowledge and attitudes. These are associated with the idea of adding value and are expressed by behaviors that a person manifests at work and by consequences of those behaviors. Competency-based management, in turn, makes it possible to consistently detect individual capacities realized by employees as developed and that enable them to carry out their functional activities, identifying gaps among those desired and existing ones, proposing permanent development and placing them in practice to add value to the organization. For development of this study, an extensive bibliographic research was carried out, which considered the dimensions of competence that are interdependent and encompass technical issues, cognition and attitudes related to work and also performance of human resources with regard to the subject in question.